Agro-economic efficiency of immature cowpea-radish intercropping systems in semiarid environment - Azevedo, Iara Beatriz Silva; Bezerra Neto, Franciso; Lima, Jailma Suerda Silva de; Chaves, Aridênia Peixoto; Silva, Josimar Nogueira da; Barros Júnior, Aurélio Paes; Nunes, Renato Leandro Costa (Pesquisa Agropecuaria Brasileira, 2021)
The objective of this work was to evaluate the agro-economic efficiency of immature cowpea-radish intercropping systems in a semiarid environment in Brazil. The experiments were carried out in two cropping seasons, in a randomized complete block design with four replicates. The treatments consisted of a 4x2 factorial arrangement for the combination of four cowpea (Vigna unguiculata) cultivars (BRS Tumucumaque, BRS Cauamé, BRS Guariba, and BRS Itaim) and two radish (Raphanus sativus) cultivars (Crimson Gigante and Zapp). The agro-economic indices – system productivity index (SPI), land equivalent coefficient (LEC), and monetary equivalent ratio (MER) – were obtained using single plots of each cultivar in each block. 'BRS Tumucumaque' and 'BRS Guariba' showed the highest productivity of immature cowpea pods, and 'Crimson Gigante' showed the highest yield of marketable radish roots. The cultivation of either 'BRS Tumucumaque' or 'BRS Guariba' cowpea with 'Crimson Gigante' radish provides a greater agro-economy efficiency and sustainability for immature cowpea-radish intercropping.